Pemanfaatan Limbah Plastik PET Sebagai Filamen Printer 3D dengan Metode Pultrusi - Wirantara, Rizky; Syamsiro, Mochamad; Mulyanti, Juriah (Infotekmesin, 2025)
Polyethylene terephthalate (PET) plastic bottle waste can be recycled into 3D printer filament through pultrusion method. Some previous studies have identified the parameters of PET recycled filament, but have not yet deeply examined the effect of the combination of parameters including the level of roughness. This study aims to evaluate the effects of variations in bed and head temperatures and printing speed on the dimensions of 3D-printed PET filament, to analyze defects, and to assess surface roughness. The results showed that the best products were found at a head temperature of 265°C, a bed temperature of 80°C, and a speed of 35 mm/s. The dominant defects that appeared were under & over-extrusion, weak infill, and layer separation and splitting. Minimal defects were obtained at a head temperature of 265°C and 260°C with a bed temperature of 80°C at a speed of 35 mm/s. The lowest surface roughness results were in class N10, namely Ra = 16.137 µm. This study indicates that optimized parameters produce high quality, making PET a sustainable alternative material.